Some crucial issues on the translation of poetic discourse from Chinese to English - Chan, Sheung Wai@Sherry (Penerbit UKM, 2003)
This paper introduces the concepts of poetic discourse, translation and poetic translation before exploring the theories and strategies involving the translation of poetic discourse. Most theories developed are supported by examples extracted from the English version of my Chinese poems. They are attached to this thesis as appendixes with the target-language text (TT), source-language text (ST) and the ST in Mandarin Pinyin form. Subsequent to the development of theories and strategies in the areas of word level equivalence and above word level equivalence, a thorough analysis of two translated poems of mine entitled ‘A Butterfly in the Web’ and ‘A Dead Dove’ and one line of ‘A Cat’s Meditation’ is presented to display all the relevant theories and strategies in application. The paper hypothesizes that translation of poetic discourse from Chinese to English would involve metaphrasing, substitution, addition, omission, alteration, creation, re-creation, adoption of general words and prefixes and suffixes, rephrasing, restructuring and overall interpretation, transformation, transcreation and compensatory techniques. It is important to know whether the translation should be author-centered, reader-centered or translator-centered, and social and cultural matters thus become crucial in the process of translation. A good poetic translator needs to be a good mediator between the two languages and cultures, a psychologist and a poet at the same time.